STUDI KASUS : IMPLEMENTASI ASUHAN KEPERAWATAN PADA NY.N (G1P0A0) YANG MENGALAMI HIPEREMESIS GRAVIDARUM PADA KEHAMILAN TRIMESTER I - Laras Indrianti, L (2022)
Background: In early pregnancy, pregnant women experience excessive nausea and vomiting or Hyperemesis Gravidarum. Hyperemesis Gravidarum is a condition of severe and prolonged nausea and vomiting during the first trimester of early pregnancy caused by psychological factors of increased levels of the hormone HCG (Human Chorionic Gonadothropin). The study was conducted to determine the causative factors and how to treat Hyperemesis Gravidarum with nursing care in the incidence and risk due to Hyperemesis Gravidarum. Methods: this study uses a case study method in implementing nursing care for Ny.N (G1P0A0) who experienced hyperemesis gravidarum in the first trimester of pregnancy in the Pejuang area, Medan Satria District, Bekasi City on 03 Agust 2021- 05 Agust 2021. Data collection was carried out by interview, observation and physical examination, as well as documentation. Result : the main nursing diagnosis is nutritional deficit related to nausea. Measurements using a nausea and vomiting questionnaire, namely PUQE-24. Nursing interventions carried out by managing nausea, giving lemon aromatherapy and monitoring vital signs. Implantation of nursing actions according to priorities that have been made and equipped with intervention from subsequent diagnoses, within 3x24 hours the problem of excessive nausea and vomiting can be resolved. Conclusion : Nursing care uses PUQE-24 meansurement and SOAP documentation. Keywords : Pregnancy, Hyperemesis Gravidarum, Nursing Care